Labeled or Learned? Youth in Indo-Nepal Cross-Border Crime - KC, Dipesh Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2017)
The purpose of this paper is to examine that the youths learned crime and labeled as offenders in Nepal's Tarai, bordering Northern Indian States Bihar and Uttar Pradesh. Various studies, Government and media reports have demonstrated the overwhelming involvement of Tarai-youths in Indo-Nepal cross-border crime as a threat to the security of the Border Society. However, youths learned crime and labeled as criminals in the Indo-Nepal border areas. Youths, especially from 'backward' social class and caste, have their limitation and their young age and suppression by the state and oligarch portray them as the vulnerable is crime. Regard to the Indo-Nepal cross-border crime, social and political factors contribute to the environment viable for learning crime.Dhaulagiri Journal of Sociology and Anthropology Vol.11, 2017; 164-183